The Effect of Vibration Frequency on the Physical and Mechanical Properties of the Material and the Phase Structure of the Pump Part - O.V. Ivanova; V.V. Savinkin; A.K. Tuleshov; A.V. Sandu; P. Vizureanu (Archives of Metallurgy and Materials, 2025)
The article solves the scientific and technical problem of studying the effect of vibration loads on the phase structure of the material and the durability of a centrifugal pump. It was found that the natural frequencies of the impeller (>100 Hz) are 75% higher than the operating speed of the structure (25 Hz), which indicates sufficient rigidity of the wheel structure for the selected materials 12Cr7Mn3SiC. The scientific novelty is represented by the established dependences of changes in the frequency range of vibrations leading to the formation of stresses, a decrease in the physico-mechanical properties of the phase structure of the material from dynamic loads of different forms of vibrations. The optimal range of permissible frequency oscillations of the system and the object that are not in the resonant state is justified. The theoretical significance is reflected in the systematization of structural and frequency-vibration factors affecting the formation of fatigue stress concentrations and the origin of microcracks in the phase structure of perlite. At a distance of 3 mm from the crack, a transition to a more dispersed structure is established, the characteristic size of ferritic grains decreases to 5-10 μm. It was found that at a distance of less than 100 μm from the crack, the hardness increases (~240 HV for ferrite and ~260 HV for perlite). Thus, cyclic loads of vibrational frequencies led to grain grinding, an increase in hardness and the appearance of a crack in the most loaded part of some samples. The acquired knowledge allows us to predict defects with high accuracy at the stage of pre-destruction of the molecular bonds of the material structure.